PENGARUH BUDAYA TIONGHOA TERHADAP KULINER DI KOTA MEDAN - Rudiansyah Rudiansyah; Tuti Sartika Sijabat (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2022)
This article was entitled ‘The Influence of Chinese Culture on Culinary in Medan City.’ This study was aimed to analyze the influence of Chinese culture on the culinary in Medan and to analyze the absorption words used in the culinary names. This research used qualitative research method and describe the field data descriptively. The theoretical basis used to analyze the problem is the theoretical basis of acculturation. Data obtained through the results of open interviews, field observations and literature review. The results showed that the process of acculturation of Chinese ethnic food in the community in Medan City was initiated by the interaction that began with trade and communication activities. The acculturation of Chinese ethnic food to Medan's culinary delights can be interpreted from the spices and food names that use some borrowing words from Chinese into Indonesian.Keywords: chinese culture; acculturation; culinary; absorption words; medan city